PERBANDINGAN STRATEGI INKUIRI TERBIMBING DENGAN PROBLEM SOLVING TERHADAP PEMAHAMAN KONSEPTUAL DAN ALGORITMA SISWA DENGAN KEMAMPUAN BERPIKIR ILMIAH RENDAH - Priyasmika, Rendy (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2019)
Abstract One of the high school chemistry materials that contains concrete concepts, abstracts and involves mathematical calculations is solubility and solubility product (Ksp). Conceptual understanding is usually expressed in short sentences while understanding algorithms is expressed by mathematical equations. Both of these understandings are closely related to one another so that to teach them requires the right learning strategies. Guided inquiry learning strategies and Problem Solving are thought to be able to improve the conceptual understanding and algorithm understanding of students with Low Scientific Thinking Ability. This study aims to determine differences in conceptual understanding with algorithm understanding of students with KBIR that are taught with guided inquiry strategies and Problem Solving. This study uses a quasi-experimental design with posttest only control group design. Data from the conceptual understanding and algorithm test results obtained from the test using 20 multiple choice questions with a reliability coefficient of 0.71 and content validity of 93.17%. Data analysis using t test and Product Moment correlation at a significance level of 5%. The results show that The learning outcomes of student with low scientific thinking ability that learned by guided inquiry’s strategy is higher than the students that learned by problem solving’s strategy and The understanding of algorithms of students with low scientific thinking ability is higher than conceptual understanding both of which that learned by guided inquiry strategies and problem solving strategies. Keywords: guided inquiry, problem solving, conceptual understanding, algorithm understanding, scientific thinking ability